Rett syndrome: Revised diagnostic criteria and nomenclature - Jeffrey L. Neul; Kaufmann, Walter E.; Glaze, Daniel G.; Christodoulou, John; Clarke, Angus J.; Bahi-Buisson, Nadia; Leonard, Helen; Bailey, Mark E. S.; Schanen, N. Carolyn; Zappella, Michele; Renieri, Alessandra; Huppke, Peter; et al. (Annals of neurology, 2010)
Objective Rett syndrome (RTT) is a severe neurodevelopmental disease that affects approximately 1 in 10,000 live female births and is often caused by mutations in Methyl‐CpG‐binding protein 2 (MECP2). Despite distinct clinical features, the accumulation of clinical and molecular information in recent years has generated considerable confusion regarding the diagnosis of RTT. The purpose of this work was to revise and clarify 2002 consensus criteria for the diagnosis of RTT in anticipation of treatment trials. Method RettSearch members, representing the majority of the international clinical RTT specialists, participated in an iterative process to come to a consensus on a revised and simplified clinical diagnostic criteria for RTT. Results The clinical criteria required for the diagnosis of classic and atypical RTT were clarified and simplified. Guidelines for the diagnosis and molecular evaluation of specific variant forms of RTT were developed. Interpretation These revised criteria provide clarity regarding the key features required for the diagnosis of RTT and reinforce the concept that RTT is a clinical diagnosis based on distinct clinical criteria, independent of molecular findings. We recommend that these criteria and guidelines be utilized in any proposed clinical research. Ann Neurol 2010